Thermomechanical Strength of Anodic Alumina Layers on Aluminum Alloys - SHULGOV, V.; SOKOL, V. (PHYSICS, CHEMISTRY AND APPLICATIONS OF NANOSTRUCTURES, 2015)
The heat resistance study of anodic alumina layers made by the open circuit potential measurements and electron microscopy is presented. The crack growth resistance of the anodic alumina layers depending on the initial aluminum alloy composition and the anodization regimes are discussed.